General Construction of Efficient Circular Weakly Balanced Repeated Measurements Designs - Mehmood, Qaisar; Rasheed , Kashif; Khadija Noreen; Rashid Ahmed; Berihan R. Elemary (Scientific Inquiry and Review, 2022)
Weakly balanced repeated measurements designs (RMDs) are used to balance out residual effects where minimal balanced RMDs cannot be obtained. RMDs are equally important in periods of both equal and unequal sizes. There should be a general procedure to construct these designs. In this article, some generators are developed for the general construction of efficient minimal circular weakly balanced RMDs.